IMPLEMENTASI PENDIDIKAN KARAKTER KEDISIPLINAN SISWA MELALUI KEGIATAN EKSTRAKURIKULER PRAMUKA - Fitri, Rini Ainur; Kamidjan, Kamidjan; Wiyadi, Heru (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2020)
The Indonesian nation has recently experienced a decline in the quality of the nation’s character, especially in discipline so that it is necessary to plant and apply character education as early as possible to children. One of the excellent extracurricular activities to form the character of student discipline is the scouting activity. The purpose of this study was to find out and describe the process of implementing student discipline character education through scout extracurricular activities. The approach used is qualitative descriptive type with data collection techniques using interview, observation, questionnaire and documentation. Data analysis in this research was carried out by collecting data, reducing data, presenting data and drawing conclusions. The results of this study, in the process of implementing disciplined character education through scouting activities namely by giving examples of exemplary attitudes to students, not giving physical punishment, teaching and learning activities carried out using the principle of spring but humor. The results of the process of implementing disciplined character education for students by using the interview and observation methods are more controlled attitude of delinquency on student, more discipline on time, self discipline, discipline in asking permission, discipline in obyeing school rules. While from the questionnaire method the results obtained are that the discipline implemented through scout activities is in the category of very disciplined with the percentage system 93,16%.